TUTURAN INTEROGATIF DALAM BAHASA SMS MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNIVERSITAS RIAU - Mariana Mariana; Auzar Auzar; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTInterrogative utterances are very important in communicating. Interrogative utterances able to convey the message the author or speaker so that the reader or listener can receive the message as intended by the writer or speaker. The problems that I researched in this study is what are interrogative sentences used in SMS? how politeness used in SMS? and how the meaning of interrogative utterances in the SMS?. This study aims to analyze and describe the types of sentences, politeness, and the meaning of interrogative utterances in SMS language students of Indonesian language and literature education class of 2010. The method used in this research is descriptive method, a method that is used to explain the data obtained in the study as they are using the techniques of data collection, record, and documentation. The application of techniques and documentation noted that the SMS is used to collect research material was then analyzed according to the research problem. The results of the study there were 71 SMS interrogative sentences with the help of question words (what, who, how, and when), 50 SMS requesting recognition of interrogative sentences answer yes or no or yes or no, interrogative sentences 3 SMS requesting an answer in the form of reasons , 8 SMS interrogative sentences in the form of an opinion, and 10 SMS that confirmed the interrogative sentence. In terms of kesantunnanya there were 10 SMS and 15 SMS manners that are not polite. In terms of narrative meaning there are 16 SMS command meaning, the meaning of the solicitation SMS 7, 5 SMS the meaning of the request, meaning persilaan 1 and 1 SMS ban meaning. The results of this study indicate that the use of interrogative utterances in SMS language students of Indonesian language and literature education FKIP Riau University class of 2010 has not polite.Keyword: Interrogative utterances, SMS language.